Pembangunan Karakter Unggul Melalui Lagu Anak-anak Indonesia di RA Uswatun Hasanah Sumedang - Wily Mohammad; Nabilla Ryca Maulidiyah (Universitas Darunnajah, Jakarta, Indonesia, 2023)
This qualitative research aims to explore the impact of Indonesian children's song singing activities at RA Uswatun Hasanah, Sumedang, on the character formation of young children. This activity focuses on introducing Indonesian children's songs which contain moral messages and positive values. In this activity, the researcher also described the atmosphere and reactions of the children when participating. The research results show that this activity has great potential in helping build the character of young children in an interactive and meaningful way. The children responded positively to this activity and felt they knew more about Indonesian songs and their meanings. In conclusion, the activity of singing children's songs at RA Uswatun Hasanah has a positive impact in introducing Indonesian cultural values, fostering a sense of togetherness, and building children's characters such as the greatness of God, a sense of humility, recognition of numbers and colors, safety, love. affection, as well as social interaction. Future research can further explore the long-term impact of this activity on the character formation of young children and other aspects that may be affected.